2014
DOI: 10.3917/mav.073.0107
|View full text |Cite
|
Sign up to set email alerts
|

Une analyse philosophique du management de la RSE : de la difficile conciliation entre l'ordre économique, l'ordre juridique et l'ordre moral

Abstract: International audienceCorporate Social Responsibility (CSR) has with the economy and the morality ambiguous relations in need of clarification. This article proposes to question the role of CSR on different levels : economic and moral. Based on the distinction of orders of moral philosophy by Pascal and on its reworking proposed by Comte-Sponville (2004), we show that CSR may belong to the legal order and guide the economic order while being limited by the moral order. This hierarchy of orders enables managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…The application of nanoshells in both imaging and therapy approach has shown promising results for specific cancerous cells. In their in vitro study, Loo et al demonstrated first detecting by imaging and then thermally ablating human breast cancer cells that overexpress HER2 using immunotargeted nanoshells that have been designed to both scatter and absorb light within the NIR [127]. Schwartz et al proposed an in vivo study of the minimally invasive treatment of canine prostate cancer in male dogs using 150 nm in diameter spherical gold-over-silica nanoshells with an absorption region that peaks near 800 nm.…”
Section: Nanoshells/nanocompositesmentioning
confidence: 99%
“…The application of nanoshells in both imaging and therapy approach has shown promising results for specific cancerous cells. In their in vitro study, Loo et al demonstrated first detecting by imaging and then thermally ablating human breast cancer cells that overexpress HER2 using immunotargeted nanoshells that have been designed to both scatter and absorb light within the NIR [127]. Schwartz et al proposed an in vivo study of the minimally invasive treatment of canine prostate cancer in male dogs using 150 nm in diameter spherical gold-over-silica nanoshells with an absorption region that peaks near 800 nm.…”
Section: Nanoshells/nanocompositesmentioning
confidence: 99%
“…Elle concilie les différents ordres d'intérêts qui traduisent les stratégies d'engagement sociétal développées par Berger-Douce (2007) sous forme de matrice, dont l'objectif est de faire évoluer les schémas mentaux des dirigeants entrepreneurs. L'adoption d'une démarche RSE, comme le notent Frémeaux et Noël (2014), servirait les intérêts économiques de l'entreprise en répondant à ses besoins de légitimation interne et externe. Ce qui correspond à une logique utilitariste de la RSE (Porter et Kramer, 2011 ;Biwolé Fouda, 2014).…”
Section: La Cognition Managériale Des Dirigeants De Pme à L'égard De La Rseunclassified